Influence of remaining coronal structure and finish line on the fracture strength of roots restored with metallic posts - Bruno Carlini-Jr; Doglas Cecchin; Gisele Damiana da Silveira Pereira; Luis Alexandre Maffei Sartini Paulillo (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The purpose of this study was to evaluate the fracture strength of roots that were prosthetically restored with metallic posts with or without any remaining coronal structure and with different finish lines. Sixty bovine incisors were sectioned below the cementoenamel junction, endodontically treated, and randomly divided into six experimental groups (n = 10) containing teeth with or without any remaining coronal structure, and with a beveled shoulder, a bevel, or a shoulder finish line design. The metallic posts were luted with dual-cured resin cement. The cores were made with composite resin, and metal crowns were cemented with zinc phosphate cement. The specimens were subjected to a tangential compressive load (135º angle) at a crosshead speed of 0.5 mm/min until failure, using a universal testing machine. The fracture strength data were analyzed using the ANOVA and LSMeans (least square means) tests (α= 0.05). The data indicated that the teeth with 2 mm of remaining coronal structure showed the highest fracture strength values when compared with the teeth without any remaining structure (p < 0.05). As to the different finish line designs, the highest fracture strength values were obtained for the beveled shoulder, followed by the bevel and then by the shoulder designs (p < 0.05). It may be concluded that, to increase fracture strength, a beveled shoulder and 2 mm of remaining coronal structure are the ideal conditions.